2021
DOI: 10.3168/jdsc.2020-0070
|View full text |Cite|
|
Sign up to set email alerts
|

Organic zinc supplementation in early-lactation dairy cows and its effects on zinc content and distribution in milk and cheese

Abstract: Zinc (Zn) is an important dietary ingredient for human and animal health. Our previous study found that feeding organic Zn to dairy cows increased Zn content in milk. In this study, supplementation of organic Zn significantly increased Zn content in both raw milk and mozzarella cheese. Most Zn was retained in cheese during cheese making. The results indicate that feeding organic Zn is beneficial for increasing Zn content in milk and cheese and that most Zn remained in cheese during cheese making and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
4
3
1
Order By: Relevance
“…In the current study, cows fed Zn supplementation have 2mmol/L higher Zn content in milk compared with control group (Figure 1). In agreement with a previous study that feeding Zn in the cows diet increased Zn and fat content in milk [12]. No significant differences in the titers IgG binding LPS at week 1 after calving were observed between the 2 groups maybe due to high immune status of these cows.…”
Section: Resultssupporting
confidence: 92%
“…In the current study, cows fed Zn supplementation have 2mmol/L higher Zn content in milk compared with control group (Figure 1). In agreement with a previous study that feeding Zn in the cows diet increased Zn and fat content in milk [12]. No significant differences in the titers IgG binding LPS at week 1 after calving were observed between the 2 groups maybe due to high immune status of these cows.…”
Section: Resultssupporting
confidence: 92%
“…Dairy cows fed additionally 59 mg of zinc daily raised milk zinc levels by 3.0% [ 32 ], whereas a daily supplement of 41 mg of additional zinc via lemongrass enhanced milk zinc concentrations by 2.09% in LG-D. Similar to previous studies [ 33 , 34 ], the current study showed that daily LG-D and PL-D containing 119 and 80 mg zinc improved milk zinc by 2.09% and 1.05%, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…The effect of fat removal was significant (P < 0.05) only for Mo, Co, Ti, Cr, and Sr (Table 2 and Table 3), indicating that the fat fraction of donkey milk carries a small but significant proportion of the mentioned elements, and no or very small amounts of Zn, Cu, Mn, Se, Li, B, and Rb (Table 4 and Table 5). Our results are in agreement with those on cow milk, in which fat is reported to carry a small percentage of total Zn (<2%), Cu (2%), Mn (1%), and Se (1%), but they differ from data on human milk, where between 15% and 18% of Zn, Cu, and Mn is associated with the fat fraction (Fransson and Lönnerdal, 1983;Lönnerdal et al, 1985;Debski et al, 1987;Van Dael et al, 1991;Xu et al, 2021). The essentiality of Mo is due to its requirement for the activity of a few Mo-containing enzymes, including xanthine oxidoreductase (XOR) in its 2 forms: xanthine dehydrogenase (XDH; EC 1.17.1.4) and xanthine oxidase (XO; EC 1.17.3.2); the association of XOR (XDH/XO) with milk fat globule membrane is well known in cow milk (Harrison, 2006;Silanikove and Shapiro, 2007).…”
Section: Elements Associated With Fatsupporting
confidence: 90%
“…Approximately 8% of milk Rb is associated with casein (Table 4 and Table 5). Compared with our results, the proportion of elements associated with casein (colloidal) in cow milk are reported to be similar for Zn (85-95% of total) and Mn (67-71%), but lower for Cu (45%; Fransson and Lönnerdal, 1983;Singh et al, 1989;Gulati et al, 2018;Xu et al, 2021). A higher proportion of milk Se (54-71%) is reported to be associated with casein in cow milk (Van Dael et al, 1991;Gulati et al, 2018).…”
Section: Elements Associated With Caseinsupporting
confidence: 49%